Distingsi dan Identitas Islam pada Madrasah: Tinjauan Kebijakan Kurikulum Madrasah - Ainun Hakiemah; Siswoyo Aris Munandar Sudirman (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2020)
Madrasa was born as the answer for the restlessness of pesantren on the existence of schools established by the dutch. After the independence of Indonesia, madrasas were still regarded as fringe classes. In early 1970s, the transformation of madrasa began to be initiated. In 1975, SKB 3 ministers which sets the content of religious lessons in declining madrasa appeared. This research is a literature study that examines the distinction and Islamic identity of the madrasa by reviewing the curriculum policy since the inception until the decline of KMA No. 184 in 2019. The results showed that the distinction and Islamic identity of the madrasa was still not optimal in producing the output of the Tafaqquh Fiddin, due to the large amount of subjects inserted within the curriculum by the ruling government. Although the equal position of madrasa in the national education constellation has been achieved, the marginalization of religious sciences in Madrasa has not ended. Meanwhile, students who strongly hold Tafaqquh Fiddin are needed at the time of the teenage radicalism.